2023
DOI: 10.1021/acssuschemeng.2c05639
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Graphene Formation Induced by Tribochemical Reaction for Sustainable Lubrication

Abstract: Graphene is widely applied as lubricating materials owing to its superior tribological performances. However, its complex synthesis process causes environmental pollution and increases production cost. In the current work, we developed a facile strategy to construct a sustainable lubricant system by generating graphene in situ, which avoided the complicated graphene synthetic process. The novel lubricant system is constructed by introducing cyclopropanecarboxylic acid (CPCa) and metal particles (nickel and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…X-ray photoelectron spectrometry (XPS) is utilized to further study the chemical valence state and element composition of the worn surface (Figure ). The binding energies at approximately 284.8, 285.4, and 288.6 eV in the C 1s spectrum are ascribed to C–C, C–O/N, and CO bonds separately (Figure a) . The three peaks at around 531.4, 532.1, and 533.0 eV in the O 1s spectrum correspond to the Fe–O, C–O, and CO bonds, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…X-ray photoelectron spectrometry (XPS) is utilized to further study the chemical valence state and element composition of the worn surface (Figure ). The binding energies at approximately 284.8, 285.4, and 288.6 eV in the C 1s spectrum are ascribed to C–C, C–O/N, and CO bonds separately (Figure a) . The three peaks at around 531.4, 532.1, and 533.0 eV in the O 1s spectrum correspond to the Fe–O, C–O, and CO bonds, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 95%
“…The binding energies at approximately 284.8, 285.4, and 288.6 eV in the C 1s spectrum are ascribed to C−C, C−O/N, and C�O bonds separately (Figure 8a). 41 The three peaks at around 531. 8c).…”
Section: Impacts Of Multifactor Variables On Tribologicalmentioning
confidence: 99%
“…As it is well known that the friction and wear on the interacting surfaces of the mechanical systems engender mechanical inefficiencies and failures, leading to enormous economic loss. 56,57 The exploitation and application of high-performance lubricants are an effective strategy to resolve the above-mentioned problem. Among that, the functional additives are the critical component for endowing the lubricants with excellent anti-wear, antioxidation, and anti-corrosion performances.…”
Section: Resultsmentioning
confidence: 99%
“…As it is well known that the friction and wear on the interacting surfaces of the mechanical systems engender mechanical inefficiencies and failures, leading to enormous economic loss 56,57 . The exploitation and application of high‐performance lubricants are an effective strategy to resolve the above‐mentioned problem.…”
Section: Resultsmentioning
confidence: 99%
“…Tribology experiments showed that the addition of 0.1 wt% of this composite reduced the friction coefficient and the wear diameter by 40% and 36%, respectively. Feng's team built a sustainable lubrication system [16] by generating graphene in situ, thus avoiding the complex graphene synthesis process. A new lubrication system was constructed by introducing cyclopropane carboxylic acid (CPCa) and metal particles (nickel and copper) into the base oil.…”
Section: Introductionmentioning
confidence: 99%